Os sites estrangeiros e as zonas de sombra do jornalismo brasileiro - Boatini Junior, Danton José (Universidade do Vale do Rio dos Sinos, 2022)
The present thesis consists of an analysis of the coverage that foreign websites operating in Brazil made of topics considered of national interest. For this, the research addressed the content produced by four vehicles: BBC Brasil, Deutsche Welle Brasil, El País Brasil and The Intercept Brasil. We consider the information brought to the public by these sites as a device, in the Foucauldian definition, that faces a dispute of meanings with the content conveyed by the hegemonic media. The main objective of this work was to identify and analyze the elements of coverage and practices of international sites that establish more complex connections in the narrated events. The theoretical conduction of this work is based on theories of the event, particularly on Foucault's concept of eventualization. The methodology applied was based on the combination of multiple case studies and analysis of journalistic coverage, combined with in-depth interview. Three events of national repercussion were chosen so that we could analyze the coverage: the 130th anniversary of the Abolition of Slavery, in 2018; the Acampamento Terra Livre, in 2019; and Fire Day, as the episode that triggered the increase in the number of fires in the Amazon became known, in 2019. Indigenous issues, the memory of slavery and the preservation of the environment are among the themes that, according to the bibliography researched, can be identified among the shadow zones of national journalism. The conclusions of this work are based on the analysis of these reports, on the interviews granted by the editors responsible for the analyzed vehicles and on the bibliographic review.
Keywords: Jornalismo digital; Acontecimento; Sites estrangeiros; Zonas de sombra; Digital journalism; Event; Foreign websites; Shadow zones; ACCNPQ::Ciências Sociais Aplicadas::Comunicação